2000
DOI: 10.1021/ac991289+
|View full text |Cite
|
Sign up to set email alerts
|

Development of Binding Assays in Microfabricated Picoliter Vials:  An Assay for Biotin

Abstract: A homogeneous binding assay for the detection of biotin in picoliter vials was developed using the photoprotein aequorin as the label. The binding assay was based on the competition of free biotin with biotinylated aequorin (AEQ-biotin) for avidin. A sequential protocol was used, and modification of the assay to reduce the number of steps was examined. Results showed that detection limits on the order of 10(-14) mol of biotin were possible. Reducing the number of steps provided similar detection limits but onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Results of the dose-response curve indicated that decreasing concentrations of cortisol, and corresponding increasing concentrations of free antibody, resulted in an increase in the bioluminescent signal from the conjugate (Figure 4). One may initially assume that increasing the amount of antibody available to bind the conjugate would result in sterically hindering aequorin and, thereby, reduce its bioluminescence, as shown in the homogeneous aequorin-based assay for biotin (21). However, a similar homogeneous response to ours, wherein signal increased with increasing antibody concentration, was found by Lewis and colleagues when they studied the response of an aequorin-thyroxine conjugate to increasing concentrations of antithyroxine antibody (22).…”
Section: Discussionsupporting
confidence: 61%
“…Results of the dose-response curve indicated that decreasing concentrations of cortisol, and corresponding increasing concentrations of free antibody, resulted in an increase in the bioluminescent signal from the conjugate (Figure 4). One may initially assume that increasing the amount of antibody available to bind the conjugate would result in sterically hindering aequorin and, thereby, reduce its bioluminescence, as shown in the homogeneous aequorin-based assay for biotin (21). However, a similar homogeneous response to ours, wherein signal increased with increasing antibody concentration, was found by Lewis and colleagues when they studied the response of an aequorin-thyroxine conjugate to increasing concentrations of antithyroxine antibody (22).…”
Section: Discussionsupporting
confidence: 61%
“…The integration of such structures with fluids and biological materials is enabling multiple applications. For example, small volume reaction containers are being considered for high‐throughput screening, (Grosvenor et al , 2000; Angenendt et al , 2005), single molecule enzymology (Rondelez et al , 2005; Rissin and Walt, 2006), and analyses of single cells (Cooper, 1999; Johannessen et al , 2002). These reaction containers are also being developed for the cell‐free synthesis of proteins (Nojima et al , 2000; Tabuchi et al , 2002; Yamamoto et al , 2002; Angenendt et al , 2004; Kinpara et al , 2004; Mei et al , 2005).…”
Section: Nanomaterials: From Individual Elements To Cell‐like Complexitymentioning
confidence: 99%
“…Self-contained micropumps are preferred for manipulating a minute amount of fluid with high precision in a microfluidic systems [9]. Lab-on-a-chip applications often require the manipulation control of of fluid volume on the order of 1 pL [10][11][12]. To avoid dead volume, a micropump should be integrated on the same chip with other components.…”
Section: Introductionmentioning
confidence: 99%